Generation and Reaction of Functional Alkyllithiums by Using Microreactors and Their Application to Heterotelechelic Polymer Synthesis. Issue 60 (9th September 2019) - Nagaki, Aiichiro; Yamashita, Hiroki; Tsuchihashi, Yuta; Hirose, Katsuyuki; Takumi, Masahiro; Yoshida, Jun‐ichi
Abstract: Flow microreactors enabled the successful generation of various functional alkyllithiums containing electrophilic functional groups, as well as the use of these alkyllithiums in subsequent reactions. The high reactivity of these series of reactions could be achieved by the extremely accurate and selective control of residence time. Moreover, integrated flow microreactor systems could be used to successfully synthesize heterotelechelic polymers with two functionalities, one at each end, via a process involving controlled anionic polymerization initiated by functional alkyllithium compounds, followed by trapping reactions with difunctional electrophiles. Abstract : Flow microreactors enabled the successful generation of various functional alkyllithiums containing electrophilic functional groups, as well as the use of these alkyllithiums in subsequent reactions (see figure).